Ethno-Cultural Diversity and Human Rights : Challenges and Critiques. - Pentassuglia, Gaetano (International Studies in Human Rights Ser., 2017)
What is the role of ethno-cultural groups in human rights discourse? Under international human rights law, standards are unclear and ambivalent, while traditional analyses have often failed to elucidate and unpack the conceptual, legal, and policy complexities involved. In Ethno-Cultural Diversity and Human Rights , prominent experts chart new territory by addressing contested dimensions of the field. They include the impact of collective interests on rights discourse and nation-building, international law's responses to group demands for decision-making authority, and concerns for immigration, intersectionality, and peacebuilding. Drawing from diverse scholarship in international law, legal and moral philosophy, and political science, this volume will be essential reading for scholars and practitioners of human rights, diversity, and conflict management.